The life histories of Meridialaris chiloeensis (Demoulin, 1955) (Ephemeroptera: Leptophlebiidae) and Gigantodax rufescens (Edwards, 1931) (Diptera: Simuliidae) on a Magellanic sub-Antarctic island (55°S) - Contador Mejias, Tamara Andrea; Kennedy, James (My University, 2016)
The life histories of Meridialaris chiloeensis (Demoulin, 1955) (Leptophlebiidae: Ephemeroptera) and Gigantodax rufescens (Edwards, 1931) (Simuliidae: Diptera) were studied in a Magellanic sub-Antarctic river in Navarino Island (55 degrees S). Both species are distributed along the whole length of the watershed. Phenology was studied in the field for a period of 12 months between August 2009 and September 2010, at a site near the river's mouth (sea level). Cumulative degree-days were calculated along the gradient at five representative altitudinal locations, starting at the river's headwaters. Samples were obtained during January of 2010 at all the remaining altitudinal locations to assess possible changes in voltinism during the austral summer season through the watershed. Results show that M. chiloeensis and G. rufescens have a bivoltine and multivoltine life cycle, respectively, at sea level. Based on degree-days obtained and field observations at the remaining stations, possible voltinism patterns are discussed for both species along the altitudinal gradient. These species are proposed as suitable long-term indicators for climate change studies in the sub-Antarctic ecoregion of Magallanes, as monitoring their responses will be important in the interpretation of changes in ecosystem function, community structure, and distributions of aquatic taxa in this region of the world.
Keywords: ephemerotera; diptera; aquatic insect; phenology; climate change; voltinism; sub-antarctic